A study on the olfactory sensory retail design of selected female clothing stores in EDSA Shangri La Plaza - Lim, Justine Louise M. (College of Home Economics, University of the Philippines Diliman, 2019)
The study determined whether Olfactory Sensory Design has an effect on the branding of female clothing stores and customer experience inside retail interiors. It showed the difference between incorporating and not including Olfactory Sensory strategies in retail design. The multiple case study approach and quasi-experimental approach were used in this research to acquire sufficient data. A Non-probability, Purposive sampling was also used to choose the four stores and respondents. A total of 27 respondents participated in this study: 22 for the questionnaire and 5 for the experiment and focus group discussion. Only two stores were used for the questionnaire and four stores were used for the experiment and focus group discussion. After gathering the data, the findings were then analysed and narrated. The study showed Olfactory Sensory Design does have an effect on the customer experience in the store. However, this sensory strategy is not the main aspect the customers notice when they go inside the retail interior. With regards to branding and marketing, Olfactory Sensory Design was proven to be a key factor that helped with customer recall of the brand. It helped develop the image of the store; making it become easily identifiable by customers in and outside of the retail space. Relating it to Interior Design, designers must take into consideration the use of such sensory retail design strategies in order to create an experiential space for the user. Finally, the researcher recommends the use of more constant olfactory strategies, more diverse set of respondents with a balanced ratio, and multiple focus group discussions to acquire more in depth findings related to this topic.